Setan Scammer : Menghindari Penipuan Online - Martha Surya Dinata Mendrofa; Asnita Julianti Waruwu; Celine Ivana Radjagukguk; Juang Saputra Zai; Arivin Ilham; Silfanny Ramadani Marunduri; Nadia Seprina Cui; Antonia Lisna Bate’e; Bobi Setiaman Hulu; Artika Memori Laoli; Majesti Mendrofa; Lusia Ingat Sri Juni Zebua (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
The main purpose of implementing the seminar with the theme (satan scammer: online fraud) is to provide education to the people of Olora village to be more aware of various modes of digital fraud. The methods used are Community Education, training, mediation, science and technology simulation, science and technology substitution. The results of the PKM explain that Fraud Mode 1: Taking Advantage of Emotions & Urgency, Fraud Mode II: False Opportunities, Prevention Strategies that can be done include Identity verification: When there is a message asking for confirmation of the request. Make sure that the message is from an official source. This can be seen from the check mark symbol in the upper right corner of the sender and use a strong and unique password: Use a strong password that is not easily guessed by anyone. The conclusion in dealing with the many online frauds today, we as young people must be more active in finding out tricks so as not to get caught in this online fraud, so that by knowing we can anticipate and fortify our parents so that they are not tempted by all forms of online fraud.